Case Report: Severe lead poisoning due to exposure to ayurvedic herbal medicine - Cericola, Gabriella; Puzik, Alexander; Salou, Sarah; Yoshimi-Nöllke, Ayami; Niemeyer, Charlotte; Feuchtinger, Tobias; Henretig, Fred; Yip, Luke; Krell, Siegfried; Hettmer, Simone (Frontiers in Pediatrics, 2025)
IntroductionLead is an environmental toxin that may cause severe damage to vital organs including the brain, kidneys, liver, and bones. Children are particularly susceptible due to higher rates of gastrointestinal absorption and detrimental effects of lead on their developing nervous systems.MethodsThis report highlights the case of a 4-year-old boy with severe lead poisoning resulting from prolonged exposure to ayurvedic herbal supplements.ResultsThe child was initially admitted with anemia, arterial hypertension, abdominal pain, and mild neurological impairment. His blood smear revealed pronounced basophilic stippling of erythrocytes. His venous blood lead level (BLL) was markedly elevated at 123 μg/dl. Detailed review of his history uncovered that he had been ingesting an ayurvedic herbal medicine for asthma. He received chelation therapy with 2,3-dimercapto-1-propanesulfonic acid and calcium disodium EDTA, resulting in rapid resolution of symptoms and gradually decreasing BLLs.ConclusionsThe case is a striking example of the significant health risks due to heavy metal contamination in ayurveda products. Better strategies to control the composition of ayurvedic products and educate families about their possible heavy metal contamination are essential to reduce the risk of lead poisoning.